Design of microstrip patch antenna with LTCC substrate for K-Band application / Nurdiyana M. Mahamud - M. Mahamud, Nurdiyana (2013)
This thesis presented the design model and simulation of 2x1 microstrip patch antenna with multilayer LTCC substrate. The antenna was design and simulation for K-band application for the range from 18GHz to 27GHz. Design of this antenna consists a circular microstrip patch antenna array with multilayer LTCC substrate in order to minimize the size of antenna and increase the gain and bandwidth for antenna performance. The specification for the proposed array antenna is it has a frequency of 22GHz, Ferro A6S LTCC substrate, an epsilon 5.9, a substrate thickness of 0.096mm and copper thickness of 0.01mm. LTCC Ferro A6S was chosen as substrate compares to other because it has high relative permittivity and multilayer structure which result in a compact size antenna. This design was simulated using Computer Simulation Tool Microwave Environment Software. The performance of the antenna was evaluated in terms of bandwidth, gain, directivity, return loss, and Voltage Standing Ratio (VSWR).